Indonesia matters : Asia's emerging democratic power - Acharya, Amitav (Hackensack, New Jersey : World Scientific, 2015)
'[This book] analyses Indonesia's foreign policy and international role under the democratic regime, with particular focus on its role as a leader of ASEAN, its relationship with the major powers of the Asia Pacific, and its place in global order of the 21st century'--
Why Indonesia matters? -- Democracy, development and stability: creating a virtuous cycle -- Indonesia and the regional architecture -- Indonesia and the major powers -- Indonesia as a global actor -- A nation on the move: Indonesian voices.
Includes bibliographical references.
Keywords: Indonesia -- Foreign relations -- 1998-; Indonesia -- Politics and government -- 1998-